(untitled) (The Pakistan Development Review, 1989)
It is my honour and privilege to present the Secretary’s report this year and to welcome you all to the Sixth Annual General Meeting of the Pakistan Society of Development Economists. It is a special honour that the President of Pakistan, Mr Ghulam Ishaq Khan, has, for the second year running found the time from his extremely busy schedule to be here with us to inaugurate the meeting. His presence here today symbolizes his continued interest and strong support for our work. Most of us know that the President himself founded this Society on October 19, 1982. He has, since that time, played an active role in the academic work of the society. It says a lot for his dedication to the profession with which he has been associated for so may decades. Honourable President, we are indeed very grateful to you for your strong support for the Society.